Seismic Diffraction Analysis of a Fluid Escape Pipe beneath the Submarine Gas Bubble Plume in the Haima Cold Seep Area - Bin Liu; Li Yang; Jiangxin Chen; Leonardo Azevedo; Tonggang Han (Geofluids)
Pipe structures are considered as fluid conduits beneath cold seeps. These structures have been observed in many geological settings and are widely accepted as the most critical pathway for fluid migration. One of such pipe structures in the Haima cold seep region is investigated herein. The pipe structure extends from below the BSR and reaches the seafloor. It is characterized by a string of events with short and strong seismic amplitudes, similar to the string of bead reflections (SBRs) associated with small-scale caves in carbonate reservoirs. This leads to the hypothesis that multiple small-scale bodies exist within the pipe structure. We test this hypothesis by analysis of diffraction waves and numerical seismic modeling. Travel time pattern analysis indicates that the diffractors within the pipe structure caused the rich diffraction waves on the shot records, and the reversed polarity indicates that the diffractors have a lower impedance than the surrounding sediments. These low-impedance bodies are interpreted as gas pockets within the pipe structures. Based on these interpretations, a conceptual model is proposed to describe the fluid migration process within the pipe. Briefly, we propose that gas pockets within the pipe structure could be analogue to the magma chambers located beneath volcanoes and this may provide a new insight into how gases migrate through the pipe structure and reach the seafloor.